INFLUENCE OF PATHOLOGICAL NARCISISM, INDECENT DRESSING AND LEARNED HELPLESSNESS ON SEXUAL HARASSMENT EXPERIENCE AMONG UNDERGRADUATE STUDENTS IN FEDERAL UNIVERSITY, OYE-EKITI, NIGERIA - Toyin Olanike Adaramoye; Samuel Toyin Akanbi; Tolulope Oluwatoyin Olayiwola-Adedoja (Psikoislamedia : Jurnal Psikologi, 2024)
This study was conducted to examine the influence of pathological narcissism, indecent dressing, and learned helplessness on the experience of sexual harassment among students of the Federal University Oye-Ekiti, Nigeria. The study adopted the correlational research design and was guided by three research questions. It involved 284 undergraduate students between the ages of 16 and 21 who were selected through stratified random sampling using the stratum of faculty. Pathological Narcissism Inventory (α=.94), The Learned Helplessness Scale (α=.91) Indecent Dressing Measure (α=.90) and Sexual Harassment Scale (α=.88) were used as measuring instruments. The data were analysed using the Pearson Product Moment Correlation and multiple regression. The results showed that narcissistic (r(284)= .372; p<1), narcissistic vulnerability (r(284)= .339; p<1), indecent dressing(r(284)= .408 p<1), and learned helplessness (r(284)= .314 p<1) positively correlated with sexual harassment. The three main predictor variables together accounted for 31% of the total variance in sexual harassment (F(4,283) = 32.858; R= .566; R2= .320; Adj. R2=.310; P<.01). In addition, the three independent variables individualistically contributed to predicting sexual harassment: learned helplessness (β=.079; t=3.036, P<.01); indecent dressing (β=.160; t=6.767, P<.01); narcissistic grandiosity (β= .184; t= 4.329, P<.01); and narcissistic vulnerability (β=.063; t=2.068, P<.05). The three independent variables explored in this study are sufficiently forceful to influence sexual harassment among undergraduates. Therefore, the study concluded that sexual harassment among undergraduates can be reduced when behaviour change agents take into account the variables considered in this study while diagnosing and preferring solutions to vulnerability to sexual harassment on campuses.